Reprogramming of Amino Acid Metabolism in Pancreatic Cancer: Recent Advances and Therapeutic Strategies - Xu, Ruiyuan; Yang, Jinshou; Ren, Bo; Wang, Huanyu; Yang, Gang; Chen, Yuan; You, Lei; Zhao, Yupei (Frontiers in Oncology, 2020)
Pancreatic ductal adenocarcinoma (PDAC) is one of the most fatal malignancies with an extremely poor prognosis. Energy metabolism reprogramming, an emerging hallmark of cancer, has been implicated in the tumorigenesis and development of pancreatic cancer. In addition to well elaborated enhanced glycolysis, investigating the role of reprogramming of amino acid metabolism has sparked great interests in recent years. The rewiring amino acid metabolism orchestrated by genetic alterations contributes to pancreatic cancer malignant characteristics including cell proliferation, invasion, metastasis, angiogenesis and redox balance. In the unique hypoperfused and nutrient-deficient tumor microenvironment (TME), the interactions between cancer cells and stromal components and salvaging processes including autophagy and macropinocytosis play critical roles in fulfilling the metabolic requirements and supporting growth of PDAC. In this review, we elucidate the recent advances in the amino acid metabolism reprogramming in pancreatic cancer and the mechanisms of amino acid metabolism regulating PDAC progression, which will provide opportunities to develop promising therapeutic strategies.